Micropropagation of Salacia reticulata - an Endangered Medicinal Plant - Dhanasri, G.; Reddy, M. Srikanth; Naresh, B.; Cherku, Devi (Plant Tissue Culture and Biotechnology, 2014)
An efficient protocol of axillary bud proliferation and direct organogenesis has been developed for Salacia reticulata, a highly important medicinal plant. Over-exploitation for its antidiabetic and antioxidant properties concentrated in roots and stem has caused it to be endangered, thereby the need for its conservation. Propagation of S. reticulata in vitro is a promising way for its conservation. To develop the micropropagation protocol, the germplasm was screened for selection of a suitable ecotype with high content of mangiferin estimated with High Performance Liquid Chromatography technique. Nodal segments were cultured on MS supplemented with different growth regulators. The most efficient shoot multiplication was obtained with the supplementation of BA and IAA (3.5 + 0.5 mg/l). Elongation of the micro-shoots was achieved by subculture every 20 days. The elongated micro-shoots were efficiently rooted in vitro on half strength MS supplemented with IBA. Plantlets were successfully established in the soil in 6 - 8 weeks and were morphologically similar to those of the source plant. The protocols developed presently for direct shoot regeneration and root-induction could be successfully applied for development of high quality planting stocks. D. O. I. http://dx.doi.org/10.3329/ptcb.v23i2.17523 Plant Tissue Cult. & Biotech. 23(2): 221-229, 2013 (December)